Concurrent Validity of Sensor Glove-Derived Measures of Upper-Extremity Motor Performance...American Occupational Therapy Association Annual Conference & Expo, April 4-7, 2019, New Orleans, Louisiana - Ellington, Allison; Adams, Richard; Armstead, Kate; Sheffield, Kristen; Standish, Heather (American Journal of Occupational Therapy)
Date Presented 06/04/19 Motion tracking sensors were added to a commercial SaeboGlove, enabling patients to engage in manual practice of instrumental activities of daily living in a computer-generated virtual world. Sensor-derived performance in completing functional tasks in the virtual environment was compared to real-world performance assessed using gold-standard measures. Statistical analysis of data collected during use by 15 stroke patients confirms the concurrent validity of the computer-generated measures. Primary Author and Speaker: Allison Ellington Additional Authors and Speakers: Richard Adams Contributing Authors: Kate Armstead, Kristen Sheffield, Heather Standish